Pengaruh Terapi Psikoreligious: Dzikir dalam Mengontrol Halusinasi Pendengaran Pada Pasien Skizofrenia yang Muslim di Rumah Sakit Jiwa Tampan Provinsi Riau - Pratiwi Gasril; Suryani Suryani; Heppi Sasmita (Universitas Batanghari Jambi, 2020)
Data from the American Psychological Association (APA) in 2010 and Riskesdas 2013 show that on the average world population has schizophrenia and 70% of schizophrenic patients experience hallucinations. One of the recommended therapies in an effort to control hallucinations is psychoreligious therapy: dhikr. The purpose of this study was to determine the effect of psycho-religious therapy: dhikr in controlling hallucinations in schizophrenia patients. The research method used is quantitative with a Quasy expriemental approach carried out on 20 respondents at the Tampan Mental Hospital, Riau Province. Researchers used the Auditory Hallucinations Rating Scale (AHRS) module and evaluation sheet before and after the intervention. The results showed that there was an effect of psychoreligious therapy: dhikr in controlling hallucinations in schizophrenic patients (p value = 0,000). The results of this study can be used as additional therapy in controlling hallucinations in patients with auditory hallucinations.